Discriminative ionic capabilities on hydrogen-bond transition from the mode of ordinary water to (Mg, Ca, Sr)(Cl, Br)₂ hydration - Fang, Hengxin (2022)
It has been a long pursuit to discriminate the ionic roles of mono- and di-valent salt solutions in modulating the hydrogen bonding network and solution properties. We attended this issue by examining the effect of concentrated YX 2 (Y[dbnd]Mg, Ca, Sr; X[dbnd]Cl, Br) solvation on O:H–O bonds transition from the mode of ordinary water to hydration in terms of the number fraction f YX2 (C) and the segmental O:H–O bond phonon stiffness shift Δω(C) with C being the solute concentration. The invariant df Y (C) / dC at C ≤ <0.05 suggests that the small Y 2+ forms a constantly-sized hydration droplet with weak responding to interference of other ions because its hydrating H 2 O dipoles screen mostly its electric field. However, the number inadequacy of the highly-ordered hydrating H 2 O dipoles partially screens the large X − . The X − ↔ X − electrostatic repulsion weakens its electric field. The concentration-trend consistency of the f YX2 (C), the solution conductivity σ YX2 (C), and surface stress (contact angle) θ YX2 (C) for YX 2 solutions clarifies their common origin of ionic polarization. However, the Jones–Dale notion disobedience of the viscosity η YX2 (C) suggests the dominance of the inter-ion repulsion.